Dampak Pandemi Covid 19 terhadap Pekerja Pariwisata di Bali - Anak Agung Gede Oka Geria (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
This research is a study of crisis caused by Covid 19 pandemic on tourism workers in Bali. The analysis technique used is descriptive qualitative, in which interviews is the main technique of data collection. This research is based on the theory of crisis management (Soemirat & Ardianto, 2005: 181), the steps of handling it, showed by Rhenald Kasali (2003: 231). The purposes of this study are to find out, 1) The opinions of tourism workers in Bali about the economic crisis caused by covid 19 pandemic. 2) What steps have been taken to deal with the economic crisis due to the COVID-19 pandemic. 3) How they view the future of the tourism business especially in their work place in Bali. The results of this study reveal: 1) The tourism workers didn’t realize that the economic crisis caused by the COVID-19 pandemic would last for a quite long time. 2) They mostly choose a strategy of adapting their lives to the current conditions, 3) They are able to isolate the crisis in the economic field only and their views of tourism in Bali would return to normal in the future but its development might be slowing down.